E-BUDDY DIGITAL ADMINISTRATION GOVERNANCE TO IMPROVE VILLAGE SERVICES - Thoyyibah, Riska Lailaturrohmah; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze and describe the implementation of the E-Buddy Digital Administrative Governance system as an effort to improve village administrative services in Bangah Village, Gedangan District, Sidoarjo Regency. Method: The research employs a qualitative descriptive approach with data collected through interviews, observations, and documentation to examine the effectiveness and challenges of E-Buddy implementation. Results: The findings show that E-Buddy has enhanced the efficiency of administrative services by accelerating correspondence processes, reducing the risk of archive loss, and facilitating electronic signatures. However, several challenges remain when assessed against six indicators: the system has legal legitimacy but lacks specific SOPs; transparency and accountability are emerging through digital records; participation is limited; performance and information flow are constrained by internet issues; fairness and capability are hindered by uneven apparatus competence; and inclusivity remains low due to limited community engagement. Novelty: This study provides new insights into the digital transformation of village governance, emphasizing that technological innovation must be supported by procedural clarity, human resource development, and community inclusiveness to achieve sustainable digital governance at the village level.